2010
DOI: 10.1007/s00520-010-0913-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy outpatients’ unplanned presentations to hospital: a retrospective study

Abstract: Chemotherapy outpatients have significant unmet needs following treatment, indicating an urgent need for improved continuity of care and better integration of primary and tertiary health care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
4
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 26 publications
10
114
4
9
Order By: Relevance
“…Study participants reported four primary gaps in cancer care delivery, including poor doctor-patient communication, insufficient attention to conversations about prognosis, lack of care coordination, and lack of access to care locations. Despite efforts to improve patient-provider communication regarding goals of care and symptom management, 8,9,[24][25][26][27] patients and caregivers noted persistent deficiencies, 7,28,29 consistent with previous studies. 2,5,10,11 Study participants identified three practical solutions to reduce these care gaps, including use of (1) nonphysician health personnel (eg, community health workers, patient navigators); (2) alternative care formats (eg, telephone-based care); and (3) extending community-based care locations (eg, home visits, chemotherapy delivery).…”
Section: Discussionsupporting
confidence: 80%
“…Study participants reported four primary gaps in cancer care delivery, including poor doctor-patient communication, insufficient attention to conversations about prognosis, lack of care coordination, and lack of access to care locations. Despite efforts to improve patient-provider communication regarding goals of care and symptom management, 8,9,[24][25][26][27] patients and caregivers noted persistent deficiencies, 7,28,29 consistent with previous studies. 2,5,10,11 Study participants identified three practical solutions to reduce these care gaps, including use of (1) nonphysician health personnel (eg, community health workers, patient navigators); (2) alternative care formats (eg, telephone-based care); and (3) extending community-based care locations (eg, home visits, chemotherapy delivery).…”
Section: Discussionsupporting
confidence: 80%
“…Unplanned presentations and admissions for cancer patients are common and cause congestion and delays for other patients requiring scheduled treatments [1]. They have a negative impact on patients and carers and put undue strain on health care resources and expenditure [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…22, 23 Through characterization of potentially avoidable hospitalizations in patients with cancer, we sought to establish a conceptual framework for the study of potentially avoidable oncology hospitalizations and to enhance the knowledge base that informs the design of future interventions.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%